2015
DOI: 10.1111/acer.12853
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of the Amsterdam Beverage Picture Set: A Controlled Picture Set for Cognitive Bias Measurement and Modification Paradigms

Abstract: BackgroundAlcohol research may benefit from controlled and validated picture sets. We have constructed the Amsterdam Beverage Picture Set (ABPS), which was designed for alcohol research in general and cognitive bias measurement and modification in particular. Here, we first formulate a position on alcohol stimulus validity that prescribes that alcohol‐containing pictures, compared to nonalcohol‐containing pictures, should induce a stronger urge to drink in heavy drinkers than in light drinkers. Because a perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
99
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 41 publications
8
99
0
3
Order By: Relevance
“…All picture pairs were matched by size and colors (see Figure 1). All stimuli originated from the Amsterdam Beverage Picture Set (ABPS [33]). Attentional bias scores for Stay and Go trials were computed by respectively subtracting the average reaction time for correct trials with the arrow at the location of the alcoholic picture from the average reaction time on correct trials where the arrow was at the location of the nonalcoholic picture.…”
Section: Methodsmentioning
confidence: 99%
“…All picture pairs were matched by size and colors (see Figure 1). All stimuli originated from the Amsterdam Beverage Picture Set (ABPS [33]). Attentional bias scores for Stay and Go trials were computed by respectively subtracting the average reaction time for correct trials with the arrow at the location of the alcoholic picture from the average reaction time on correct trials where the arrow was at the location of the nonalcoholic picture.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we designed a mobile based App program called cognition addiction therapy (CAT) by combining cognitive training and cognitive bias modification. Furthermore, studies have showed that enhanced drug-related choice can be demonstrated even for pictorial stimuli [25], with simple passive pictures might induce stronger cognitive biases while active pictures presenting drug use related context might induce a stronger urge for drugs [26]. MA use related pictures were integrated into the App programs, aiming to address both cognitive impairment and cognitive bias in MUD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Borrowing from the definition of test validity by Borsboom, Mellenbergh, and Van Heerden (), and translating these considerations to the concept of stimulus validity (Pronk, van Deursen, Beraha, Larsen, & Wiers, ), stimuli would be considered as valid “if variations in the stimuli causally produce variations in the attribute” under investigation (Pronk et al, , p. 2048). For instance, since we want the stimuli to activate addiction‐related concepts (such as memory contents) and provoke addiction‐related responses (e.g.…”
Section: Introductionmentioning
confidence: 99%